The community participation on infrastructures and facilities updating data of Teratak Village, Rumbio Jaya - Agus Ika Putra; Soewignjo Agus Nugroho; Fajar Restuhadi; Ari Sandhyavitri; Febrizal Febrizal; Iswadi Hasyim Rosma (University of Merdeka Malang, 2023)
Village Information System (SID) is an implementation of e-government by the village government. The right of village communities to get real-time information can be hampered due to the skills and abilities of human resources and out-of-date information. The activity is focused on updating Village data and facilities through survey primary data collection. The results of the survey are up-to-date data, are integrated, and can be accessed online. The process of entering data into the SID will be continued by the Village Government Officials who manage the SID, for this reason, there is a need for a special briefing for Village Government Officials in a training activity in updating data on village facilities and infrastructure. Workshops in the form of training, practice and question and answer were carried out with feedback in the form of questionnaires before and after the workshop to assess the success of the program. The survey data that is input to the SID includes health facilities, religious facilities, agriculture, animal husbandry, plantations, educational facilities, village tourism potential, and potential disasters along with their evacuation points. This updated data is expected to be a reference for compiling the Teratak Village Development and workshop activities have been able to improve the ability of village government.